MBRS-61. IN VIVO METABOLOMICS REVEALS A POTENT COMBINATION THERAPY FOR MYC-DRIVEN MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Hanaford, Allison; Poore, Brad; Alt, Jesse; Slusher, Barbara; Eberhart, Charles; Raabe, Eric
Abstract: The MYC oncogene is associated with aggressive forms of medulloblastoma. MYC promotes oncogenesis partly by altering cellular metabolism. We hypothesized that MYC-driven medulloblastoma would be sensitive to the glutamine metabolic inhibitor 6-diazo-5-oxo-l-norleucine (DON). We found that 10uM DON treatment increases apoptosis by up to 280% (p<0.04) as compared to vehicle control in four MYC-driven medulloblastoma cell lines. Once-weekly DON therapy increased median survival by up to 246% (p<0.004) in three different MYC-driven medulloblastoma orthotopic xenograft models. We performed in vivo stable isotope resolved metabolomics (SIRM) on two MYC-driven medulloblastoma tumor models and found that tumors from DON treated animals had decreased production of asparagine (p<0.016), leading us to hypothesize that treatment with asparaginase would enhance DON efficacy. Asparaginase breaks down asparagine into aspartate and ammonia and is a commonly used therapy for pediatric leukemia and lymphoma. In MYC-driven medulloblastoma cell lines, treatment with 4uM DON or asparaginase alone did not significantly increase apoptosis by cleaved caspase-3 immunofluorescence or cleaved-PARP western blot. The combination of low-dose DON and asparaginase increased apoptosis by up to 577%, more than observed with 10uM DON alone (p<0.0001). We hypothesized that asparagine depletion would induce apoptosis via the uncharged tRNA/endoplasmic reticulum stress response. Western blotting revealed that the combination of DON and asparaginase increased expression of the transcription factor ATF4 and the pro-apoptotic protein CHOP, which are critical components of the uncharged tRNA response. These data suggest that DON and asparaginase could be a powerful therapeutic combination for treating MYC-driven medulloblastoma and possibly other MYC-driven malignancies.